A practical guide to make the case for sustainable investment in well-being and health. (13th November 2019) - Stielke, A; Ashton, K; Dyakova, M; Bellis, M
Abstract: : Growing health, inequity, economic and environmental challenges threaten the well-being of present and future generations. Current investment policies and practices are unsustainable and result in high human, social, economic and environmental costs. Countries require the tools to build the case for investment in areas of greatest need by applying evidence-informed practice. A practical guide with tools and resources was developed on how to develop an evidence-informed product to make the case for investment in well-being and health equity. Stakeholder interviews with national and international experts in health policy, equity, economics and social sciences were conducted to inform the outline of the guide and identify enablers for creating evidence-informed products. An evidence review gathered tools and resources on how to translate and communicate public health evidence into policy and practice. An international cross-sector expert consultation assured relevance and transferability of the guide across countries, contexts and policies. The guide aims to prevent disinvestment in health and increase investment in prevention as well as mainstream cross-sector investment to target the wider determinants of well-being and health equity. It outlines how to synthesise, translate and communicate public health and health economic evidence into policy and practice and proposes a step-by-step approach following four key phases (i) project scoping and planning, (ii) evidence gathering, synthesis and design, (iii) dissemination and communication, (iv) monitoring and evaluation. The guide presents information to develop an evidence-informed product to make the case for sustainable investment in an innovative and informative way for use by a range of stakeholders. It accounts for policies and contexts and is communicated in a way that is accessible for decision-makers, easy to use and available as hard copy and interactive version. Key messages: Investing in well-being and health equity drives and enables sustainable development. Making the case for investment in health equity requires a well-planned, evidence-informed approach.